2014
DOI: 10.1186/1477-5751-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric differences in the surgical outcomes of patients with traumatic acute subdural hematoma

Abstract: BackgroundOur assumption that prognosis of patients with traumatic acute subdural hematoma (ASDH) does not differ significantly according to the hemispheric laterality has never been verified.MethodsA review of the charts/radiographic images of 61 adult traumatic ASDH patients (33 left/28 right) was conducted. Intergroup comparison was made on the demographics, autonomic/laboratory data, and outcomes (90-day mortality rate). Based on the presence of concomitant brain contusion, patients were further quadrichot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The only previous study on hemispheric outcome difference in ASDH found a higher frequency of intractable brain swelling and mortality rate in patients with a left-sided ASDH. This difference was only significant if patients presented with a concomitant contusion [11], similar to our findings. Other studies found significant asymmetry of the autoregulatory index between the injured and intact hemisphere in TBI patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The only previous study on hemispheric outcome difference in ASDH found a higher frequency of intractable brain swelling and mortality rate in patients with a left-sided ASDH. This difference was only significant if patients presented with a concomitant contusion [11], similar to our findings. Other studies found significant asymmetry of the autoregulatory index between the injured and intact hemisphere in TBI patients.…”
Section: Discussionsupporting
confidence: 91%
“…Laterality of the haematoma does not play a major role in the decision for surgery, as is reflected in the absence of consideration in TBI guidelines [10]. Furthermore, only a limited amount of research regarding this laterality is available [11][12][13][14]. This contrasts with stroke laterality where numerous studies have shown an association of worse outcome in dominant hemispheric infarction [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative management is appropriate for patients with traumatic acute SDH without neurological deficits and radiographical evidence of brain compression because acute SDH is absorbed or sequestered, and disappears eventually in most cases. [ 1 2 3 4 ] However, delayed neurological deterioration due to hematoma increase during transition from acute to subacute stage has been reported in the literature,[ 5 6 7 8 ] with varying degree of frequency: while Bajsarowicz reported that only 6.5% of acute SDH patients who received initial conservative management sustained delayed hematoma increase requiring hematoma evacuation,[ 6 ] the frequency was as high as 35% in a cohort reported by Kim et al . [ 7 ] The mechanism of hematoma increase during transition from acute to subacute stage has been attributed to invasion of CSF into hematoma driven by osmotic gradient generated by the fibrinolytic products in the hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Prognosis of traumatic acute subdural hematoma (SDH) patients is determined mostly by hematoma volume, concomitant brain parenchymal damage, and patient age. [ 1 2 3 4 ] For patients who are neurologically intact and have only a small hematoma volume on imaging studies, conservative management is justified: acute SDH is absorbed gradually in such circumstances. [ 4 ] However, caution is required in cases which exhibit conversion of SDH from acute to subacute stage because delayed hematoma increase and neurological deterioration may occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation